The Impact of Capital Lease Implementation on Corporate Financial Statements: Theoretical Analysis and Case Studies - Putra, Ongky Parmadhie; Khaddafi, Muamar (Sahabat Publikasi, 2024)
This article explores the concept of capital lease in accounting and its implications for a company's financial statements. A capital lease, also known as a finance lease, is recognized as both an asset and a liability on a company's balance sheet. This research discusses the differences between capital lease and operating lease, as well as their impacts on a company's financials. Through literature review and case study analysis, this article provides insights into the advantages and challenges companies face when implementing capital leases. The findings suggest that while capital leases strengthen balance sheets by recognizing assets and liabilities, they also affect profitability through higher interest and depreciation expenses. Proper understanding and management of these implications can help companies make more informed financing decisions.